2011
DOI: 10.3758/s13414-011-0129-3
|View full text |Cite
|
Sign up to set email alerts
|

Attentional load inhibits vection

Abstract: In this study, we examined the effects of cognitive task performance on the induction of vection. We hypothesized that, if vection requires attentional resources, performing cognitive tasks requiring attention should inhibit or weaken it. Experiment 1 tested the effects on vection of simultaneously performing a rapid serial visual presentation (RSVP) task. The results revealed that the RSVP task affected the subjective strength of vection. Experiment 2 tested the effects of a multiple-object-tracking (MOT) tas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 27 publications
1
32
0
Order By: Relevance
“…For example, coherent full-field visual motion stimuli elicit the sensation of self-motion such as the illusory feeling of motion when sitting in the stationary train while it is only the neighboring train that pulls out of the station in the direction opposite to the felt motion. However, people react differently to full-field motion stimuli, and in laboratory experiments additional tasks can weaken the strength of vection (Seno et al, 2011). Prefrontal regions may exert their influence over the vestibular cortical regions through its indirect connection with the premotor areas and the temporal lobes (Damasio and Anderson, 2003).…”
Section: Affective Processes and Disordersmentioning
confidence: 99%
“…For example, coherent full-field visual motion stimuli elicit the sensation of self-motion such as the illusory feeling of motion when sitting in the stationary train while it is only the neighboring train that pulls out of the station in the direction opposite to the felt motion. However, people react differently to full-field motion stimuli, and in laboratory experiments additional tasks can weaken the strength of vection (Seno et al, 2011). Prefrontal regions may exert their influence over the vestibular cortical regions through its indirect connection with the premotor areas and the temporal lobes (Damasio and Anderson, 2003).…”
Section: Affective Processes and Disordersmentioning
confidence: 99%
“…As noted previously, vection perception has been shown to be weakened when adequate attention is not given to the surrounding stimuli ( 21 ). Furthermore, it was also noted previously that the effective visual fi eld of subjects has been observed to be reduced in conditions of higher altitudes ( 10 ).…”
Section: Discussionmentioning
confidence: 87%
“…Because previous studies have shown that wider effective visual fi elds can induce stronger vection perception ( 2 ) and that vection requires attentional resources ( 21 ), a wider visual stimulus fi eld and increased attentional resources should be necessary to produce stronger vection perception. However, in hypoxia conditions, both of the characteristics are unavailable.…”
mentioning
confidence: 99%
“…A study by Seno et al (2011b) showed that increases in attentional load reduced vection, suggesting that the induction of vection might require attentional resources. It is possible that, during treadmill walking, subjects were devoting attentional resources to staying upright on the moving treadmill, which could have detracted from the visually induced illusion of selfmotion.…”
Section: Discussionmentioning
confidence: 99%